Evaluation of hydraulic characteristics of core flow monitoring mechanism for PFBR. (March 2017) - Shivakumar, N.S.; Bekkenti, Nagaraju; Suresh Kumar, S.; Ravichandran, N.; Vinod, V.; Padmakumar, G.; Rajan, K.K.
Highlights: Any flow blockage in subassemblies can lead to overheating of fuel pins in them. Sodium flow mainly through fresh subassemblies (SAs) is measured in PFBR. Hydraulic characteristics of core flow measurement is carried out. Experimental studies indicate 58.5% of coolant flow through sensor measuring region. A different measuring geometry for flow measurement in blanket and storage SAs. Abstract: Sodium flow through the fuel, blanket and storage subassemblies will be measured in Prototype Fast Breeder Reactor (PFBR) by the Core Flow Monitoring Mechanism (CFMM) during its commissioning. CFMM is planned to be placed on the top of the subassembly for the sodium flow measurement. This will monitor the flow allocation through different sub-assemblies and will infer flow blockage in subassembly if any. A portion of the sodium flowing through the subassembly will flow through the CFMM and the rest will flow through the lateral safety flow path provided at the subassembly top. The sodium flow through the CFMM will be measured by an eddy current flow sensor. For estimating the sodium flow through the subassembly from the measured sodium flow through CFMM, the hydraulic characteristics of the subassembly top portion and CFMM was established by experiments in water medium. It is estimated that 58.5% of the coolant flow passes through the CFMM for measuring sodium flow through fuel subassemblies and the rest passes through the lateral holes in the subassembly head. In case of measurement of flow through the blanket and storage subassemblies, 52% of the coolant passes through CFMM and the rest passes through the lateral holes. The data obtained from the water experiments were used to validate the numerical model of the same. This paper gives the details of the experimental and numerical studies carried out to characterize the core flow monitoring device for PFBR.